Behcet's disease: demographic and genetic aspects (a literature review) - Fatima Ismailovna Izmailova; Z S Alekberova (Современная ревматология)
A review of literature focused on Behcet's disease (BD) is presented. BD is systemic vasculitis of unknown etiology affecting multiple organs. BD is endemic in the countries along the Eastern Mediterranean coast and the areas of Central and East Asia. We report the data on BD prevalence in different regions and the effect of population migration on BD incidence rate. Patients were found to be younger at the onset of the disease in Arab countries, Turkey, and Israel (19.9; 25.6; and 26 years, respectively) than those in East Asia countries (31.7 years). We summarized the data attesting to the genetic susceptibility in BD patients: HLA B51-positive individuals, family aggregation observed when studying twins, etc. The clinical polymorphism in BD patients was shown to depend on their region of residence and ethnicity. The data of a series of large cohort studies are reported; the frequencies of the international criteria of BD in the US and Japanese patients are compared in these studies. The question regarding the need for cross-sectional population-based and case-control studies using the standard criteria and clear definition of ethnicity is brought up in some publications.